Exploring Foreign Muslim Tourist Preferences in Halal Tourism: A Study of Indonesia’s Halal Market - Taufik Romadon; Lizar Alfansi; Effed Darta; Ferry Tema Atjama; Parwito Parwito; Muhammad Eid Balbaa; Revanth Kumar Guttena (Journal of Digital Marketing and Halal Industry, 2025)
This study investigates the preferences of foreign Muslim tourists in Indonesia's halal tourism sector, with a particular focus on their expectations regarding halal accommodation, products, destinations, and regulations. This study aims to identify deficiencies in policy implementation, infrastructure development, and international marketing that impede Indonesia's potential as a prominent global halal tourism destination. A qualitative research methodology was employed, incorporating interviews and focus group discussions with seven stakeholders: religious scholars, tourism operators, business owners, and foreign Muslim tourists. Data were analyzed using NVivo 12 and Atlas 7 software to extract key themes and insights. The findings revealed significant inconsistencies in halal certification, infrastructure, and international marketing strategies. Foreign Muslim tourists prioritize halal-certified services, cultural authenticity, and inclusivity. However, the inadequate implementation of halal standards, limited halal-friendly infrastructure, and ineffective international promotion efforts constrain Indonesia's capacity to attract more Muslim travelers. Policy recommendations include the enhancement and standardization of halal certification processes, improvement of halal-friendly infrastructure, and implementation of targeted international marketing campaigns. Strategies to promote inclusivity among non-Muslim tourists have also been proposed to support sustainable growth. This study offers novel perspectives by integrating cultural identity, contemporary tourism approaches, and global expectations. It examines the intersection of faith-based travel and accessibility and presents practical suggestions for establishing Indonesia as a leading destination for halal tourism.